Forming of the system of primary documents services in agriculture in Soviet Lithuania - Zinkevičienė, Julija (Knygotyra, 1988)
The article is devoted to the results of the analysis of expert evaluation of the databases that are received in our republic. These databases differ according to their value for the specialists of agriculture. The general contents of these databases do not coincide with the requirements of those specialists, but it is possible to use special themes in the agricultural information systems. The article shows the main list of referred publications. The publications that are received by libraries are identified as well. Some of them are working with the aid of IBM. It is possible to show the percentage of the publications received in our republic that are included in the databases of VNIITEISM.